Implementation of Javanese Gamelan Music Therapy (Gending Karawitan) on Anxiety Levels in Elderly People at the Tresna Werdha Pagar Dewa Social Welfare Institution in Bengkulu City in 2025 - Dzaky, Yafi Arya; Ramlis , Ravika; Aprianti, Delta (Multidisciplinary Journals, 2025)
The elderly experience a decline in bodily functions that can lead to balance disorders and anxiety, with a fairly high prevalence, especially among those aged 65 and above. WHO data (2022) shows that the number of elderly people continues to increase, including in Indonesia, which has reached 11.75% of the total population. One non-pharmacological intervention to reduce anxiety is This case report aims to determine the implementation of Javanese gamelan music therapy (gending karawitan) on anxiety levels in the elderly at the Tresna Werdha Pagar Dewa Social Welfare Institution in Bengkulu City in 2025. This study used a descriptive method with a case study using interviews and observations on one client with anxiety as the research respondent. From the results of the study conducted over three consecutive days of playing Javanese gamelan music (gending karawitan), there was a decrease in anxiety scores from 39 (moderate anxiety) to 35 (mild anxiety). Javanese gamelan music therapy (gending karawitan) can be an effective non-pharmacological intervention in reducing anxiety in elderly patients with anxiety. This intervention can be considered as part of gerontological nursing services in social institutions.